On comparison of fracture energy measured for six hot mix asphalt composite mixtures using force-load line displacement and force-crack mouth opening displacement curves at intermediate temperatures and different loading rates - Amirdehi, H. R. Fattahi; Ghoreishi, S. M. N.; Aliha, M. R. M.; Hesami, Saeid; Haghighatpour, Pegah Jafari; Choupani, Naghdali (Wiley, 2024)
There are two methods for determining the fracture energy (Gf) of hot mix asphalt (HMA) composites at intermediate temperatures: (i) load-crack mouth opening displacement (CMOD) and (ii) load-load line displacement (LLD) curves. The effects of these two methods on the Gf values of different HMA mixtures are investigated at different loading rates and temperatures. A large number of semicircular bend (SCB) specimens were tested under mode I at different temperatures of 5 degrees C, 15 degrees C, and 25 degrees C and loading rates of 1, 5, 10, and 50 mm/min. The three-dimensional (3D) fracture energy surface plots obtained from the tests revealed that both temperature and loading rate have noticeable effects on the fracture energy, such that Gf values generally increased by increasing the loading rate and reducing the temperature. Also, the Gf values measured by the LLD method were higher than those by the CMOD method for lower temperatures and lower loading rates (i.e., below 10 mm/min). For the higher loading rates, the Gf values determined by the CMOD method were higher than those by the LLD method. Furthermore, the HMA type had meaningful influences on the variations of Gf at different temperatures and loading rates. Fracture energy (Gf) dependency of HMA mixtures to the force-CMOD or force-LLD methods was demonstrated. The Gf value increases by increasing the loading rate and decreasing the temperature. At higher loading rates, the CMOD method provided a higher Gf value. Gf was the function of mixture types and environmental and testing conditions.
Keywords: force-CMOD curve; force-LLD curve; HMA mixtures; mode I fracture energy; temperature and loading rate effects